Temporary diplopia upon hyoscine-N-butyl bromide administration: case report - Migliorini R (Dove Medical Press, 2013)
R Migliorini, R Malagola, M Mafrici, R Spena, L ArricoDepartment of Sense Organs, University of Rome "La Sapienza", Rome, ItalyAbstract: Hyoscine-N-butyl bromide is a widely used antispasmodic belonging to the belladonna alkaloid class of semisynthetic quaternary ammonium compounds. These compounds exert a spasmolytic action on the smooth muscles of the bile-gastrointestinal tract, genitourinary tract, salivary glands (xerostomia), and also on the visual apparatus – in particular, the irido-ciliary complex. As a consequence, they provoke collateral effects such as mydriasis and accommodation disturbances. We report the case of a 23-year-old woman who complained of not only "dry mouth" but also "cloudy vision" and a "diplopia", both of temporary type, 2 hours after oral administration of hyoscine-N-butyl bromide.Keywords: hyoscine-N-butyl bromide, accommodation disorders, temporary diplopia, fusion alteration, vertical strabismus